Diseño e implementación de un sistema semiautomático en la cizalladora de planchas y perfiles del taller mecánico del Área de la Energía, las Industrias y los Recursos Naturales no Renovables de la Universidad Nacional de Loja. - Medina Poma, Patricio Antonio (2014)
The sheared is the operation of out a sheet of metal along a straight line. The sheared is used for reducing big sheets in short ones. It´s executed in a machine called shear or scissors that can be operated: manual, mechanic, hydraulic, electric and pneumatically. This research has like target to determine the necessary parameters for designing, building and implementing a system of semiautomatic drive that best suits the shearing of machine shop of Área de la Energía, las Industrias y los Recursos Naturales No Renovables of Universidad Nacional de Loja, that permit reducing of considerable way the effort for operating this machine, as well as for avowing some risks for being in contact with the machine for improving the work. Considering technic and economic parameters was necessary to do a full scan of the sheared taking into account the numbers of operators and the necessary effort for realizing a cut, moreover of investigating the market about the costs of a semiautomatic machine and so whether it is wise to invest in the implementation of a new drive system. With the data and obtained valves in the scan, we select the hydraulic system, as the best and the most convenient drive, so following with the design and choosing the basic and indispensable components of a hydraulic circuit, for proceeding with its subsequent construction and implementation in the machine. This research defines the parameters of design and the operation of a shear allowing cut of metal sheets without a big effort, then of the implementation we verify that the new drive can be: more efficient, safe and reliable.